2014
DOI: 10.1128/microbiolspec.plas-0022-2014
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Biopharmaceuticals

Abstract: Plasmids are currently an indispensable molecular tool in life science research and a central asset for the modern biotechnology industry, supporting its mission to produce pharmaceutical proteins, antibodies, vaccines, industrial enzymes, and molecular diagnostics, to name a few key products. Furthermore, plasmids have gradually stepped up in the past 20 years as useful biopharmaceuticals in the context of gene therapy and DNA vaccination interventions. This review provides a concise coverage of the scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 196 publications
1
20
0
Order By: Relevance
“…A large number of DNA vaccines have undergone clinical trial and their general safety demonstrated 18 . Consistent with those studies, this Phase I clinical trial clearly demonstrates that 3 intradermal immunizations with COR-1 is safe and well-tolerated in humans at doses up to 1 mg, with no vaccine-related moderate or severe TEAEs or SAEs observed.…”
Section: Discussionsupporting
confidence: 72%
“…A large number of DNA vaccines have undergone clinical trial and their general safety demonstrated 18 . Consistent with those studies, this Phase I clinical trial clearly demonstrates that 3 intradermal immunizations with COR-1 is safe and well-tolerated in humans at doses up to 1 mg, with no vaccine-related moderate or severe TEAEs or SAEs observed.…”
Section: Discussionsupporting
confidence: 72%
“…Naturally occurring plasmids mediate a variety of biological functions including bacterial conjugation, transfer of disease-causing virulence genes and transfer of resistance genes to various detrimental environmental factors, such as antibiotics, radiation and heavy metals. With the discovery of restriction enzymes [2,3] and subsequent development of recombinant DNA technology [4], plasmids have become versatile tools in basic biological research and biotechnology development for biomedical, agricultural and industrial applications [5][6][7][8][9][10][11]. With the advent of de novo DNA synthesis [12] and the decreasing cost and rising efficiency of relevant technologies, more and more researchers have switched to de novo synthesis of their desired plasmids to save resources and time required for traditional cloning methods [13,14].…”
Section: Methods Summarymentioning
confidence: 99%
“…DNA vaccine is stable, safe in handling, cost-efficient and easy to manufacture (Prazeres and Monteiro, 2014). Importantly, DNA vaccine can activate both CD4+ and CD8+ T cell response, as well as innate immune response due to the recognition of double stranded DNA structure by cytosolic sensors (Tang and Pietersz, 2009;Ori et al, 2017).…”
Section: Dna Vaccinementioning
confidence: 99%